The Effect of the ICARE Learning Model in Distance Learning on the Mathematical Problem Solving Ability of SMK Negeri 2 Karawang Students - Hikmatuprilla, Al Wanita Imani; Ambarwati, Lukita; Wijayanti, Dwi Antari (Journal of Medives : Journal of Mathematics Education IKIP Veteran Semarang; Vol 5 No 2 (2021): Journal of Medives : Journal of Mathematics Education IKIP Veteran SemarangDO - 10.31331/medivesveteran.v5i2.1706, 2021)
This study aims to obtain empirical information about the effect of implementing the ICARE learning model (Introduction, Connect, Apply, Reflect, Extend) in distance learning on students’ problem-solving abilities at SMK Negeri 2 Karawang . The research method used was a quasi-experimental with posttest-only control group design. The population in this study were all class X students at SMK Negeri 2 Karawang . Sampling using Cluster Random Sampling to determine the affordable population and Simple Random Sampling to determine the sample. Class X TB 1 was chosen to be the experimental class and class X TB 3 was selected as the control class. The results of the statistical hypothesis testing were then carried out using the the-test of two independent samples with a significant level of 5% concluded that the mean test results of students' mathematical problem-solving abilities in the experimental class were higher than the control class. The large effect test carried out obtained the result of d = 0.8, this shows that the ICARE learning model in distance learning has a significant effect on the mathematical problem-solving abilities of students at SMK Negeri 2 Karawang on the sequence and series material. The influence given is 79% and is included in the large category. Keywords: Learning Model ICARE (Introduction, Connect, Apply, Reflect, Extend), Distance Learning, Mathematical Problem Solving Ability